Phage Display Derived Monoclonal Antibodies: From Bench to Bedside - Alfaleh, Mohamed A.; Alsaab, Hashem O.; Mahmoud, Ahmad Bakur; Alkayyal, Almohanad A.; Jones, Martina L.; Mahler, Stephen M.; Hashem, Anwar M. (Frontiers in Immunology, 2020)
Monoclonal antibodies (mAbs) have become one of the most important classes of biopharmaceutical products, and they continue to dominate the universe of biopharmaceutical markets in terms of approval and sales. They are the most profitable single product class, where they represent six of the top ten selling drugs. At the beginning of the 1990s, an in vitro antibody selection technology known as antibody phage display was developed by John McCafferty and Sir. Gregory Winter that enabled the discovery of human antibodies for diverse applications, particularly antibody-based drugs. They created combinatorial antibody libraries on filamentous phage to be utilized for generating antigen specific antibodies in a matter of weeks. Since then, more than 70 phage–derived antibodies entered clinical studies and 14 of them have been approved. These antibodies are indicated for cancer, and non-cancer medical conditions, such as inflammatory, optical, infectious, or immunological diseases. Antibody phage display has proven to be a powerful, versatile platform for antibodies discovery and development. This review will illustrate the utility of phage display as a powerful platform for therapeutic antibodies discovery and describe in detail all the approved mAbs derived from phage display.